ANALISIS MANAJEMEN KELAS DALAM PROSES BELAJAR DARING PESERTA DIDIK PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Uti Uti; Hery Kresnadi; Asmayani Salimi (Universitas Tanjungpura, 2021)
AbstractThe problem in this study is whether online learning in thematic learning cananalyze the classroom management of fourth grade students at SD KartikaPontianak City? This study aims to describe Classroom Management Analysisin the Online Learning Process of Students in Class IV Thematic Learning atSD Kartika XVII-1 Pontianak City. This study used descriptive qualitativemethod. With the research subject, the fourth grade teacher at SD Kartika XVII-1 Pontianak City. The techniques used in data collection areobservation/observation techniques, interview techniques, and documentationtechniques as data collection instruments. The implementation of learningcarried out by teachers by applying classroom management study onlinelearning process in thematic learning using qualitative descriptive methods,study online process teachers also use online lesson plans as a guide inteaching.Keywords: Classroom Management, Online Learning, Thematic Learning